Single-Domain Antibody-Based TCR-Like CAR-T: A Potential Cancer Therapy - Lichen Zhu; Xiaomei Yang; Dani Zhong; Shenxia Xie; Wei Shi; Yangzi Li; Xiaoqiong Hou; HuaYao; Huihui Zhou; Minlong Zhao; Ziqiang Ding; Xinyue Zhao; et al. (Journal of Immunology Research)
Retargeting the antigen-binding specificity of T cells to intracellular antigens that are degraded and presented on the tumor surface by engineering chimeric antigen receptor (CAR), also named TCR-like antibody CAR-T, remains limited. With the exception of the commercialized CD19 CAR-T for hematological malignancies and other CAR-T therapies aiming mostly at extracellular antigens achieving great success, the rareness and scarcity of TCR-like CAR-T therapies might be due to their current status and limitations. This review provides the probable optimized initiatives for improving TCR-like CAR-T reprogramming and discusses single-domain antibodies administered as an alternative to conventional scFvs and secreted by CAR-T cells, which might be of great value to the development of CAR-T immunotherapies for intracellular antigens.